2018
DOI: 10.1017/ice.2017.286
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Asymptomatic Clostridium difficile Among Bone Marrow Transplant Patients: A Mixed-Methods Study of Intervention Effectiveness and Feasibility

Abstract: OBJECTIVE To identify facilitators and barriers to implementation of a Clostridium difficile screening intervention among bone marrow transplant (BMT) patients and to evaluate the clinical effectiveness of the intervention on the rate of hospital-onset C. difficile infection (HO-CDI). DESIGN Before-and-after trial SETTING A 505-bed tertiary-care medical center PARTICIPANTS All 5,357 patients admitted to the BMT and general medicine wards from January 2014 to February 2017 were included in the study. Interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Based on the survey results, at least 11 peer-reviewed manuscripts based on preceptorship projects, which are distinct from the trainees’ doctoral thesis projects, were produced by the 38 students that participated in the clerkship. Some of these preceptorship-based manuscripts have already been published [3946], while others remain under peer-review. An additional 11 abstracts were submitted and accepted for presentation at either local or national meetings, and four students identified that the data generated from their project was used in the submission of a grant application.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the survey results, at least 11 peer-reviewed manuscripts based on preceptorship projects, which are distinct from the trainees’ doctoral thesis projects, were produced by the 38 students that participated in the clerkship. Some of these preceptorship-based manuscripts have already been published [3946], while others remain under peer-review. An additional 11 abstracts were submitted and accepted for presentation at either local or national meetings, and four students identified that the data generated from their project was used in the submission of a grant application.…”
Section: Resultsmentioning
confidence: 99%
“…A mixed deductive and inductive thematic analysis guided by the Systems Engineering Initiative for Patient Safety framework will be used to analyze interview data. The Systems Engineering Initiative for Patient Safety framework is a human factors engineering framework that has been used extensively in a variety of health care settings to characterize work systems and document changes to the work system following implementation of quality improvement interventions . Interview transcripts will be coded independently with tests for reliability.…”
Section: Methodsmentioning
confidence: 99%
“…The Systems Engineering Initiative for Patient Safety framework is a human factors engineering framework that has been used extensively in a variety of health care settings to characterize work systems and document changes to the work system following implementation of quality improvement interventions. [32][33][34][35] Interview transcripts will be coded independently with tests for reliability. Analyses will focus on identifying the changes (or lack thereof) that occurred in study NH work systems as a result of implementing the Wisconsin UTI Toolkit in an effort to identify key barriers and facilitators to adoption.…”
Section: Analyses Of Toolkit Adoption Measures and Determinantsmentioning
confidence: 99%
“…79 Screening transplant patients at admission for C. difficile colonization facilitates early implementation of infection prevention measures and may result in decreased horizontal transmission. 78,80 In one study of patients admitted to an inpatient hematological unit, colonization with C. difficile conferred an 11.6 times higher odds of progression to CDI compared to those without colonization. 81 Identification of these asymptomatic carriers is an opportunity for targeted risk-reduction measures, such as antimicrobial review, to reduce the risk not only for symptomatic infection but for vertical transmission as well.…”
Section: Clostridioides Difficile Infectionmentioning
confidence: 99%
“…It is unclear how to optimally use asymptomatic screening for AMS efforts without unintentionally causing inappropriate treatment from misinterpretation of tests. 80,82 Oral vancomycin prophylaxis is an attractive option to prevent CDI. Retrospective reviews suggest that primary prophylaxis in allogenic HSCT recipients is associated with significantly lower rates of CDI 83,84 and that secondary prophylaxis is effective in reducing CDI recurrence in kidney transplant patients.…”
Section: Clostridioides Difficile Infectionmentioning
confidence: 99%